Assessment of Electric Vehicle Charging Scenarios in China Under Different-temperature Conditions. (September 2021) - Huang, Peifeng; Liu, Shoutong; Zhang, Yaming; Ou, Yang; Zeng, Ganghui; Zhou, Jinjin; Bai, Zhonghao
Highlights: An assessment procedure of charging under all-temperature conditions was proposed; Five vehicles were tested and fairly graded into five degrees following the procedure; The scores show the charging performance is closely related to thermal management; The assessment can be more rigorous and efficiency at broader testing temperatures; Abstract: The variation of ambient conditions could influence the safety and performance of charging. This paper proposed an assessment procedure to evaluate the safety and performance of charging under all-temperature conditions. Through analyzing the temperature distribution all over China in the last 8 years, we chose 39 °C and -11 °C as the testing temperatures. The synthesis assessment was conducted from thermal management and charging performance aspects, following five sub-indexes: temperature rise, temperature difference, charging rate, charging quantity ratio, and charging economy. The weight distribution of sub-indexes was assigned at 40%, 10%, 40%, 6%, and 4%, respectively, by the Analytic Hierarchy Process method. Through charging tests, we found the vehicles with liquid cooling system perform good but not always better than vehicles with air cooling system in thermal management. The charging performance is closely related to thermal management. In the final score, five vehicles were graded into 5 degrees according to their scores, which testifies the efficiency and fairness of the evaluation procedure. Besides, when the testing temperatures extend to -20 °C and 50 °C, the charging performance gaps between vehicles get enlarged. It is easier to tell the difference in charging performance under such extreme testing temperatures.